Revitalising the Role of Higher Education in Encouraging Social Transformation through Sustainable Innovation-Based Services - Rustiawan, Indra; Siminto; Choerudin, Achmad (PT. LITERASI SAINS NUSANTARA, 2025)
This research aims to examine in depth how universities can revitalise their role in encouraging social transformation through community service based on sustainable innovation. Using a qualitative approach in the form of literature review and descriptive analysis, this research analyses 19 selected articles from Google Scholar and other credible online sources published between 1996-2025. The findings show that sustainable innovation in community service programmes has great potential in empowering communities, increasing local capacity, and creating systemic social impact when developed through collaboration between actors, participatory approaches, and the use of science and technology. This study is based on the Triple Helix, Diffusion of Innovations, and engaged scholarship theories that emphasise the importance of synergy between academia, community, industry, and government. Case studies in various parts of Indonesia show the success of innovation-based service models in improving community welfare in a sustainable manner. Therefore, revitalising the role of universities through innovative service not only supports the national development agenda, but also reaffirms the social function of universities as agents of change.